Validation of Cognitive Load During Inquiry-Based Learning With Multimedia Scaffolds Using Subjective Measurement and Eye Movements - Kastaun, Marit; Meier, Monique; Küchemann, Stefan; Kuhn, Jochen (Frontiers in Psychology, 2021)
Subject-method barriers and cognitive load (CL) of students have a particular importance in the complex learning process of scientific inquiry. In this work, we investigate the valid measurement of CL as well as different scaffolds to reduce it during experimentation. Specifically, we examine the validity of a subjective measurement instrument to assess CL [in extraneous cognitive load (ECL), intrinsic cognitive load, and germane cognitive load (GCL)] during the use of multimedia scaffolds in the planning phase of the scientific inquiry process based on a theoretical framework of the CL theory. The validity is analyzed by investigating possible relationships between causal (e.g., cognitive abilities) and assessment (e.g., eye-tracking metrics) factors in relation to the obtained test scores of the adapted subjective measurement instrument. The study aims to elucidate possible relationships of causal factors that have not yet been adequately investigated in relation to CL. Furthermore, a possible, still inconclusive convergence between subjective test scores on CL and objectively measured indicators will be tested using different eye-tracking metrics. In two studies (n=250), 9th and 11th grade students experimentally investigated a biological phenomenon. At the beginning of the planning phase, students selected one of four multimedia scaffolds using a tablet (Study I: n=181) or a computer with a stationary eye-tracking device (Study II: n=69). The subjective cognitive load was measured via self-reports using a standardized questionnaire. Additionally, we recorded students’ gaze data during learning with the scaffolds as objective measurements. Besides the causal factors of cognitive-visual and verbal abilities, reading skills and spatial abilities were quantified using established test instruments and the learners indicated their representation preference by selecting the scaffolds. The results show that CL decreases substantially with higher grade level. Regarding the causal factors, we observed that cognitive-visual and verbal abilities have a significant influence on the ECL and GCL in contrast to reading skills. Additionally, there is a correlation between the representation preference and different types of CL. Concerning the objective measurement data, we found that the absolute fixation number is predictive for the ECL. The results are discussed in the context of the overall methodological research goal and the theoretical framework of CL.